Raising Performance Through Information Technology and A Good Work Environment - Salsabila, Arizta; Suratman, Andriyastuti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This study aims to determine how extent the information technology, work environment, and job satisfaction experienced by employees can affect employee performance. This study uses a quantitative method by distributing questionnaires to 215 Yogyakarta employees working at start-up companies, using a purposive sampling technique. The research data were processed using SPSS software version 29.0. The analytical methods used are a t-test, coefficient of determination test, multiple linear regression analysis, and path analysis. The results of this study are that information technology has a positive and significant effect on employee performance, the work environment has a positive but not significant impact on employee performance, and information technology and work environment have a positive and significant effect on job satisfaction. Job satisfaction can mediate the relationship between information technology and the work environment on employee performance.